Advanced nursing practice roles: Closing the knowledge gap. Issue 3 (March 2019) - Ko, Arthur; Burson, Rosanne; Mianecki, Therese
Abstract : To realize organizational goals centered on cost and quality, healthcare leaders should understand the potential of and provide support for advanced nursing roles. This research project assessed participants' understanding of the distinction between APRN and clinical nurse leader roles, as well as the roles of doctorally prepared nurses.